A Systematic Review of the Evidence Base for Instructional Choice in K–12 Settings. (May 2017) - Royer, David J.; Lane, Kathleen Lynne; Cantwell, Emily D.; Messenger, Mallory L.
We conducted this systematic literature review to explore the current evidence base of instructional choice, a low-intensity, teacher-delivered strategy to support academic engagement and decrease challenging behaviors. Specifically, we focused on school-based settings, applying quality indicators (QIs) and evidence-based standards of the Council for Exceptional Children (CEC). Included articles met five criteria: (a) independent variables included instructional choice; (b) dependent variables included behavior (e.g., disruptive behavior, problem behavior, aggression), time on task/academic engaged time, and/or academic performance (e.g., task initiation, completion, accuracy, fluency); (c) interventions occurred with school-age students in traditional school settings; (d) the study followed an experimental design; and (e) the article was published in English in a refereed journal. Twenty-five articles (26 studies) from 13 journals met inclusion criteria. Findings indicated providing students instructional choices increased desired academic behavior while decreasing instances of disruptive behavior. Of the 26 studies, three met all QIs, with nine additional studies addressing 80% or more. Due to small participant numbers, effect sizes, and other factors in these studies, we classified instructional choice into the CEC evidence-based category of insufficient evidence . We conclude with a discussion of limitations and directions for future inquiry.